2000
DOI: 10.1074/jbc.275.11.7862
|View full text |Cite
|
Sign up to set email alerts
|

Subtypes of the Somatostatin Receptor Assemble as Functional Homo- and Heterodimers

Abstract: The existence of receptor dimers has been proposed for several G protein-coupled receptors. However, the question of whether G protein-coupled receptor dimers are necessary for activating or modulating normal receptor function is unclear. We address this question with somatostatin receptors (SSTRs) of which there are five distinct subtypes. By using transfected mutant and wild type receptors, as well as endogenous receptors, we provide pharmacological, biochemical, and physical evidence, based on fluorescence … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

11
363
2
8

Year Published

2006
2006
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 489 publications
(384 citation statements)
references
References 44 publications
(113 reference statements)
11
363
2
8
Order By: Relevance
“…45 Increased expression of SSTRs 1, 2, and 5 were observed in this study (Figure 5a). Hence, it is possible that the dimerization of SSTR4 with another SSTR isotype may affect migration or other responses of HOCs.…”
Section: Discussionsupporting
confidence: 67%
“…45 Increased expression of SSTRs 1, 2, and 5 were observed in this study (Figure 5a). Hence, it is possible that the dimerization of SSTR4 with another SSTR isotype may affect migration or other responses of HOCs.…”
Section: Discussionsupporting
confidence: 67%
“…Since we have demonstrated that inhibition of α 2B -AR cell-surface expression is mediated through dimerization of mutant and WT receptors, it is possible that the inhibitory effect of α 2B -ARm on the transport of α 2A -AR and α 2C -AR is also due to heterodimerization of α 2B -ARm with α 2A -AR or α 2C -AR. This possibility is supported by a number of observations demonstrating that closely related members of G protein-coupled receptors may heterodimerize [11,14,[37][38][39]. Furthermore, α 2A -AR and α 2C -AR indeed form heterodimers with β 1 -AR and M 3 -muscarinc receptor, respectively [40,41].…”
Section: Discussionmentioning
confidence: 76%
“…Therefore, dimers are unable to export from the ER. Dimerization has been well described for a variety of G protein-coupled receptors [9][10][11][12][13][14][15][34][35][36][37][38][39][40][41]. However, whether α 2B -AR is capable of forming homodimers has not been reported.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Using cell-based expression studies it has been previously demonstrated that SSTR1 and SSTR5 exist as monomers in the basal state. However, in the presence of SST agonists, SSTR1 and SSTR5 are able to form heterodimers with each other (Rocheville et al, 2000;Patel et al, 2002). Since M a n u s c r i p t 12 both B-and A-cells of the endocrine express multiple SSTRs.…”
Section: In Vitro Studiesmentioning
confidence: 99%